Facing disruption: Learning from the healthcare supply chain responses in British Columbia during the COVID-19 pandemic. Issue 2 (March 2022) - Zhang, Jie; Mitchell, Cheryl; Kushniruk, Andre; Guitouni, Adel
The healthcare supply chain crisis surrounding Personal Protective Equipment (PPE) during the onset of the COVID-19 pandemic presented unique and complex challenges in achieving the primary aim of supply chain management, that is, delivering the right amount of the right supplies to the right people at the right time. This article describes the key findings from a case study on PPE supply chain responses to the COVID-19 pandemic in British Columbia (BC). It highlights a set of constructive response mechanisms to potential crises along healthcare supply chain. Effective and trusted leadership, a unity of purpose, integrated and robust digital infrastructure and capabilities, consistent learning, resilience building, and environmental sensing for reliable intelligence were found to be essential for preparing, for containing, and mitigating the crisis as it evolved across various phases of crisis management.